Social Cognitive Determinants of Physical Activity in Czech Older Adults - Mudrak, Jiri; Slepicka, Pavel; Elavsky, Steriani (Journal of aging and physical activity, 2017)
We tested a social cognitive model of physical activity (PA) in the cultural context of the Czech Republic, a postcommunist central European country. In total, 546 older Czech adults (mean age = 68 years, data collected in 2013) completed a battery of questionnaires assessing indicators of PA and related social cognitive constructs, including self-efficacy, social support, and self-regulation strategies. Subsequently, a structural equation model was used to test the relationship between the social cognitive constructs and PA. Our analyses indicated an acceptable fit of the proposed model (CFI = .911; SRMR = .046; RMSEA = .073). Self-regulation was predicted by self-efficacy (β = .67) and social support (β = .23), which predicted PA (β = .45). The model explained 60.4% of the variance in PA self-regulation and 20.5% of the variance in PA participation. The results provide further evidence for the role of self-efficacy and social support in enabling PA in older adults, and suggest that this relationship is partially mediated by self-regulation.
Keywords: senioři; Self Efficacy; Cognition; cvičení; Česká republika; mužské pohlaví; sociální determinanty zdraví; Czech Republic; social support; Geriatric Assessment; Social Determinants of Health; kognice; geriatrické hodnocení; self-efficacy; ženské pohlaví; Humans; physical activity; sociální opora; older adults; Social Support; sebeuplatnění; social cognitive; Exercise; self-regulation; Female; Aged; structural equation modeling; lidé; Male